Safety and immunogenicity in humans of enterotoxigenic Escherichia coli double mutant heat-labile toxin administered intradermally - Marcela F. Pasetti; Patricia L. Milletich; Jessica A. White; Jessica Butts; Rebecca C. Brady; Michelle D. Dickey; Cassandra Ballou; Nicole Maier; Marcelo B. Sztein; Shahida Baqar; A. Louis Bourgeois; David I. Bernstein (npj Vaccines)
Abstract Enterotoxigenic Escherichia coli (ETEC) diarrhea is associated with a high burden of disease globally, for which no licensed vaccine is available. A Phase 1, double-blind, dose-escalation (0.1-2.0 µg) study was conducted to evaluate the safety and immunogenicity of double mutant heat-labile toxin LTR192G/L211A (dmLT) delivered intradermally (ID) to healthy adults. Subjects received up to three immunizations at three-week intervals. The vaccine was safe, although it induced mild local and some gastrointestinal adverse events, as well as frequent hyperpigmentation at the injection site. High levels of serum IgG and IgA, LT neutralizing antibodies, and IgG and IgA antibodies in lymphocyte supernatant were elicited post-vaccination, most prominently at the largest dose (2.0 μg). Rates of responses were the highest in subjects who received the largest dose (2.0 μg) and multiple immunizations. The ETEC dmLT vaccine was safe and highly immunogenic, inducing long-lasting systemic and mucosal responses when administered by the ID route. Trial registration Clinical Trials NCT02531685.